Fields Mathematics Education Journal - Martinovic, Dragana; Kotsopoulos, Donna; Proulx, Jerome
This international peer-reviewed online journal aims to provide open access to the range of themes that attract attention of the mathematics education community internationally. FMEJ has an international editorial board. All submissions are double-blind peer-reviewed. The views expressed or implied in the publication, unless otherwise noted, should not be interpreted as official positions of the Fields Institute for Research at the Mathematical Sciences, the founding organization of the journal. Manuscripts previously published in other journals, books or electronic venues are not accepted for review.